Novel ink for ambient condition printing of liquid crystal elastomers for 4D printing - Roach, Devin J; Kuang, Xiao; Yuan, Chao; Chen, Kaijuan; Qi, H Jerry (Smart materials and structures, 2018)
Structures capable of reversible shape changes directly after 3D printing are highly desirable for myriad of applications ranging from soft robotics to implantable medical devices. Liquid crystal elastomers (LCEs) have been studied for their large, reversible mechanical actuations in response to temperature. Recently, several efforts were carried out to direct ink write (DIW) 3D print LCE, however, these methods require high temperatures for printing and actuation. Here, we present a novel LCE ink formulation which allows LCE to be printed at room temperature with a maximum actuation temperature of 75 °C. These advantages allow the 3D printed LCEs to be integrated with other 3D printing methods and materials to create more complex shape changes. By 3D printing LCE and conductive wires, which provide Joule heating, we demonstrated an active hinge, a reversibly opening and closing box, a soft robotic gripper for pick and place, and a printed hand for sign language.